Management of Axial Spondyloarthritis – Insights into Upadacitinib - Braun J; Kiltz U; Baraliakos X (Drug Design, Development and Therapy, 2022)
Jürgen Braun, Uta Kiltz, Xenofon Baraliakos Rheumazentrum Ruhrgebiet and Ruhr University Bochum, Herne, GermanyCorrespondence: Jürgen Braun, Rheumazentrum Ruhrgebiet, Claudiusstr.45, Herne, 44649, Germany, Tel +492325592131, Email juergen.braun@elisabethgruppe.deAbstract: Although the pathogenesis of spondyloarthritis (SpA) has still not been elucidated our options to treat SpA have definitely improved in the last decades. There are two main types of SpA: (i) axial spondyloarthritis (axSpA), also covering the classical ankylosing spondylitis (AS) which is largely equivalent to radiographic (r)-axSpA but different from non-radiographic (nr)-axSpA, and (ii) peripheral SpA (pSpA) also covering psoriatic arthritis (PsA) as the main subtype. The subtype nr-axSpA has historically developed because the approval of drugs for AS did not cover forms without structural changes in the sacroiliac joints which is mandatory in the 1984 New York criteria. The definitions for axSpA are based on the 2009 Assessments in AxSpA International Society (ASAS) classification criteria. Several biologic disease modifying anti-rheumatic drugs (bDMARDs) such as the tumor necrosis factor alpha inhibitors (TNFi) and the interleukin-17-inhibitors (IL-17i) are approved mostly for the whole spectrum of SpA including axSpA and PsA but L-17i does not work in inflammatory bowel disease (IBD). Targeted synthetic (ts) DMARDs cover mainly the janus kinase (JAK)-inhibitors which have recently been developed to inhibit inflammation in several rheumatic and other immune mediated diseases such as IBD. Indeed, the physiologic mechanism of JAK-mediated signal transduction has been recognized as an important target because the inhibition of its actions was shown to successfully work as a therapeutic mechanism. There are now 4 small molecule JAK inhibitors (JAKi) that currently play a role in rheumatology with variable selectivity for the four different JAK isoforms: tofacitinib, baricitinib, upadacitinib and filgotinib. In this review, we summarize current clinical trial data and evaluate the use of the JAK1 selective inhibitor upadacitinib in the treatment of axSpA, including nr-axSpA and r-axSpA. Even though the efficacy and safety of upadacitinib over shorter periods of time has been convincing to date, long-term trials are needed to fully establish its performance and also evaluate the safety at higher doses, and its use in PsA.Keywords: ankylosing spondylitis, axial spondyloarthritis, upadacitinib, JAK inhibition